The Whipple Museum of the History of Science Objects and Investigations, to Celebrate the 75th Anniversary of R. S. Whipple's Gift to the University of Cambridge - Nall, Joshua; Taub, Liba; Willmoth, Frances (Social Sciences, 2019)
This collection of essays by noted historians provides examples of the study of the material culture of science. The essays demonstrate how the study of scientific objects offers a window into cultures of scientific practice not afforded by textual sources alone. This title is also available as Open Access on Cambridge Core.